Effect of doxercalciferol (1α-hydroxyvitamin D2) on PTH, bone turnover and bone mineral density in a hemodialysis patient with persistent secondary hyperparathyroidism post parathyroidectomy - Parisi, Muriel Solange (2003)
The efficacy and safety of the vitamin D analog, doxercalciferol (1α-hydroxyvitamin D2, 1αD2) in the treatment of secondary hyperparathyroidism in hemodialysis patients has been previously reported. We report thse effect of 16-week 1αD2 treatment on mineral metabolism and bone mineral density (BMD) in a hemodialysis patient with persistent secondary hyperparathyroidism post parathyroidectomy, resistant to previous calcitriol treatment. Levels of iPTH, bone-specific alkaline phosphatase and serum type I collagen C telopeptide were above normal at baseline and were substantially decreased with 1αD2 treatment (-92%, -63% and -53%, respectively). BMD increased in all areas: total skeleton (+6.5%), lumbar spine (+6.9%) and total femur (+4.3%). The patient showed no hypercalcemia, and phosphorus levels remained between 3.3 and 6.2 mg/dl.